Hubungan Jumlah Pengunjung, Modal Dan Jam Kerja Terhadap Pendapatan Pedagang Kaki Lima Dikawasan Water Front City Kabupaten Barito Utara - Hidayatulah, Muhammad; Nur, Muhammad Anshar (PPJP ULM, 2024)
Micro, small and medium enterprises (MSMEs) have a role in economic growth in the region. One of the MSMEs commonly found is street vendors. Especially in the Water Front City area of Muara Teweh, the income of street vendors is very varied due to certain factors.This study aims to determine the effect of factors such as the number of visitors, capital,working hours, age, and education level individually and simultaneously (simultaneously) on the income of street vendors. This research was conducted by quantitative method, where primary data was collected by questionnaire method. The results showed that the factors of capital and working hours had a positive impact on the income of street vendors. Meanwhile,the number of visitors, age, and level of education does not affect the income of street vendors.Meanwhile, the factors that were tested simultaneously (simultaneously) had a significant positive impact on the income of street vendors.